Mid-IR impurity absorption in As₂S₃ chalcogenide glasses doped with transition metals - Paiuk, A.P.; Stronski, A.V.; Vuichyk, N.V.; Gubanova, A.A.; Krys’kov, Ts.A.; Oleksenko, P.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Room temperature IR impurity absorption spectra in 1 4000 7000 cm
( 4.1 - 25um ) region for chalcogenide glasses of As₂S₃ doped with chromium (0.5,
1 wt.%) and manganese (0.1, 1, 2, 5 wt.%) have been studied. The effects of chromium
and manganese impurities on the transmission spectra are discussed.